Integration in Rome and in the Roman world : proceedings of the Tenth Workshop of the International Network Impact of Empire (Lille, June 23-25, 2011) - Impact of Empire (Organization) (2013)
Integration in the empire under the political control of the city of Rome, her princeps, and the different authorities in the provinces and cities includes processes of inclusion and exclusion. These multifaceted processes take place at various levels in society and at different places, over a long period of time. In this volume, these processes are analysed and reflected on from different perspectives. Juridical, political, social and religious points of view are articulated, elaborating on epigraphic, literary, juridical and numismatic evidence. Notions of personal and collective identities have been linked to relevant Roman realia, so that various contents of Romanitas can be defined through contextualization.